2021
DOI: 10.1002/solr.202100034
|View full text |Cite
|
Sign up to set email alerts
|

Additive Engineering toward High‐Performance Tin Perovskite Solar Cells

Abstract: Perovskite solar cells (PSCs) have emerged as one of the third‐generation photovoltaic technologies. However, the toxicity issue of the lead element in perovskite absorbers hinders their large‐scale production. Thus, exploiting lead‐free perovskite materials becomes an important solution to overcome this challenge. Among all the candidates, tin perovskites have advanced rapidly in recent years due to their low toxicity, favorable bandgap, and high carrier mobility. After a few years of development, the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 111 publications
1
37
0
Order By: Relevance
“…A‐site cations in ASnX 3 structures do not engage in forming of VB or CB but influence the energy gap by lattice contraction phenomena. Wu et al [ 59 ] determined that mixed‐cation perovskite (like FA 1− x Cs x SnI 3 ) exhibits a reduction in energy gap when Cs + doping increases. The contraction of FA 1− x Cs x SnI 3 perovskite enhances the antibonding interaction of metal–halide orbitals and transfers the VB to higher level, giving a narrow energy gap.…”
Section: Perovskite Structure Dimensionalities and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A‐site cations in ASnX 3 structures do not engage in forming of VB or CB but influence the energy gap by lattice contraction phenomena. Wu et al [ 59 ] determined that mixed‐cation perovskite (like FA 1− x Cs x SnI 3 ) exhibits a reduction in energy gap when Cs + doping increases. The contraction of FA 1− x Cs x SnI 3 perovskite enhances the antibonding interaction of metal–halide orbitals and transfers the VB to higher level, giving a narrow energy gap.…”
Section: Perovskite Structure Dimensionalities and Propertiesmentioning
confidence: 99%
“…The previous research studies have established that quantum well phenomena originated by insulating cations (like Bab or PEAb) in 2D perovskite architectures can cause efficiency reduction of deices. To resolve this issue, Wu et al [ 59 ] suggested π ‐conjugated cation PPA + to enhance the mobility in 2D tin perovskite 3‐phenyl‐2‐propen‐1‐amine (PPA) demonstrates a robust conjugated architecture overlapped by highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) which permits electron delocalization in molecule and this combination enhanced mobility of PPA 2 SnI 4 layer by three times greater than PEA 2 SnI 4 layer. [ 130,131 ] Moreover, PPA decelerated crystallization of FASnI 3 during annealing and enhanced the grains of perovskite layers subjected to the evidence that high‐density PPA cations elevate the Gibbs free energy of nucleation and promote the evolution of bigger perovskite grains.…”
Section: Materials Synthesis and Device Optimizationmentioning
confidence: 99%
“…In addition, the exclusion of Pb opens new opportunities for perovskite solar cells in applications such as building‐integrated photovoltaics (BIPV) or wearable devices. Because of the narrow bandgap, close to the ideal value (~1.34 eV) for single‐junction solar cells, and the higher carrier mobility of Sn‐based perovskites compared to Pb‐based ones, Sn is considered the most feasible replacement for Pb 1‐9 . However, when thin films are formed from Sn‐based perovskites by solution processing, problems such as nonuniform morphology and poor reproducibility appear due to rapid crystallization because of low crystallization temperatures 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the narrow bandgap, close to the ideal value ($1.34 eV) for single-junction solar cells, and the higher carrier mobility of Sn-based perovskites compared to Pb-based ones, Sn is considered the most feasible replacement for Pb. [1][2][3][4][5][6][7][8][9] However, when thin films are formed from Sn-based perovskites by solution processing, problems such as nonuniform morphology and poor reproducibility appear due to rapid crystallization because of low crystallization temperatures. 10,11 In order to solve these problems, various additives have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Defect passivation is a promising way to reduce the non‐radiative recombination loss, and many passivation agents for perovskite materials have been developed, including inorganic metallic salts (e. g., NaF, CaI 2 , KOH, and PbSO 4 ), [29–31] low‐dimensional wide‐bandgap perovskite phase, [32,33] insulating polymers, [34,35] and organic small molecules [36–40] . Among them, organic molecules offer a large structure flexibility for passivating different kinds of defect states and can adapt to a variety of perovskite compositions [41–43] . For example, the Lewis base groups with electron‐rich property such as carbonyl, pyridyl, sulfydryl, and thienyl can form coordination with the under‐coordinated Pb 2+ to passivate the deep‐level traps [44–47] .…”
Section: Introductionmentioning
confidence: 99%